A bibliometric analysis of PCSK9 inhibitors from 2007 to 2022 - Luo, Qin; Tang, Zhenchu; Wu, Panyun; Chen, Zhangling; Fang, Zhenfei; Luo, Fei (Frontiers in Endocrinology, 2023)
Background Since the approval of the proprotein convertase subtilisin/kexin type 9 (PCSK9) monoclonal antibodies for marketing in 2015, PCSK9 inhibitors have attracted significant interest in the field of cardiovascular endocrinology. A large number of clinical trials have confirmed the efficacy and safety of PCSK9 inhibitors in reducing cholesterol and the risk of cardiovascular events. No bibliometric analysis of PCSK9 inhibitors has been performed as of yet. This study aims to analyze the research trends and hotspots of PCSK9 inhibitors through bibliometric analysis. Methods We searched the Web of Science Core Collection (WoSCC) database for PCSK9 inhibitor-related publications from 2007 to 2022. Data visualization analysis was performed using CiteSpace software. Microsoft Excel and Graphpad software were used for the drawing of some tables and figures. Results A total of 1072 pieces of literature were retrieved between 2007 and 2022. The number of publications concerning PCSK9 inhibitors is growing annually. The top five countries with the most articles published were the United States, England, Canada, Italy, and France. Harvard University, Amgen, Brigham & Women’s Hospital, Harvard Medical School, and Imperial College London are the five institutions with the highest output. The Journal of Clinical Lipidology is the most popular journal in this field. The most frequently cited journal is the New England Journal of Medicine. As for authors, Sabatine MS and Giugliano RP from Brigham & Women’s Hospital have the highest number of published articles. Amgen is the funding agency for most of the research. According to keyword analysis, “low density lipoprotein”, “familial hypercholesterolemia”, “PCSK9 inhibitor”, “PCSK9”, and “efficacy” are the five keywords with the highest frequency of co-occurrence. Conclusion The past 15 years have witnessed a rapid and fruitful development of PCSK9 inhibitors. The research trend and focus for PCSK9 inhibitors are from the mechanism of reducing low-density lipoprotein cholesterol to related clinical trials. Developed countries such as the United States have contributed prominently in this area. Coronary artery and inflammation are currently at the forefront of research in the field and are in an explosion period.